Bi nanorods anchored in N-doped carbon shell as anode for high-performance magnesium ion batteries. (20th November 2021) - Cen, Yuan; Dong, Jinren; Zhu, Tingting; Cai, Xing; Wang, Xian; Hu, Bingbing; Xu, Chuanlan; Yu, Danmei; Liu, Yuping; Chen, Changguo
Highlights: Successfully developed a facile route to synthesize core-shell Bi@NC nanorods. Core-shell Bi@NC nanorods were firstly applied as anode for MIBs. Micropores in carbon matrix mitigate the large volume change of inner core Bi. Excellent Mg storage performance, especially in rate performance. Abstract: The rechargeable magnesium batteries are potentially applicable in large-scale energy storage systems because of the low costs and rich sources. But the alternative anodes for magnesium ion batteries have not been fully developed. In this work, a novel bismuth-carbon composite with bismuth nanorods anchored in nitrogen-doped mesoporous carbon matrix (Bi@NC), was prepared as anode for magnesium ion batteries by carbonizing the dopamine-coated bismuth metal precursors. The matrix facilitated the magnesiation/de-magnesiation of bismuth due to its highly electronic conductive network. Moreover, it restrained the aggregation of bismuth nanorods and serves as a buffer layer to alleviate the mechanical strain of bismuth nanorods upon magnesium insertion/extraction. As the anode for magnesium ion batteries, the Bi@NC core-shell nanorods delivered a reversible capacity of 360 mAh g −1 at the current density of 100 mA g −1, and 87 % of the initial capacity was achieved after 100 cycles. The standout rate performance is 275 mAh g −1 at the current density of 1 A g −1 . Such a good electrochemical property demonstrated the great application potential of Bi@NC as anode in magnesium ion batteries. Graphical abstract: Image, graphical abstract